The Effect of Need for Achievement dan Self Efficacy towards Interepenurial Intention - Avaqhi, Cut Febi Mutiara; Lawita, Nadia Fathurrahmi (Universitas Negeri Semarang, 2024)
This study describes a person's desire and determination to build an entrepreneurial spirit towards the relationship between the Theory of Planned Behaviour (TPB) and entrepreneurial intentions. The sample used was the entire population of 90 female students. Survey research data collection instrument using questionnaire. Interepenuerial Intention either directly or indirectly through attitude as an intervening variable. The population in this study is Batam State Polytechnic Managerial Accounting Students with a sample of 90 respondents. Data was analyzed using SEM-PLS. The results showed that the results showed (1) Negative and insignificant influence between Need for Achivement and Interpenurial Intention; (2) Positive and significant effect between Self efficacy on Interpenurial Intention; (3) Positive and insignificant effect between Self efficacy on Need for Achivement; (4) Positive and insignificant effect between Social support and Interpenurial Intention; (5) Negative and significant effect between Social support and Need for Achivement on Interpenurial Intention; (6) there is a negative and significant influence between Social support and Self efficacy on the Interpenurial Intention of female students of D4 managerial accounting at Batam State Polytechnic. These results also encourage and succeed the Problem Based Learning program for the Entrepreneurship Course.